Glycoprotein Targeted CAR-NK Cells for the Treatment of SARS-CoV-2 Infection - Christodoulou, Ilias; Rahnama, Ruyan; Ravich, Jonas W.; Seo, Jaesung; Zolov, Sergey N.; Marple, Andrew N.; Markovitz, David M.; Bonifant, Challice L. (Frontiers in Immunology, 2021)
Banana Lectin (BanLec) binds high mannose glycans on viral envelopes, exerting an anti-viral effect. A point mutation (H84T) divorces BanLec mitogenicity from antiviral activity. SARS-CoV-2 contains high mannose glycosites in proximity to the receptor binding domain of the envelope Spike (S) protein. We designed a chimeric antigen receptor (CAR) that incorporates H84T-BanLec as the extracellular moiety. Our H84T-BanLec CAR was devised to specifically direct NK cell binding of SARS-CoV-2 envelope glycosites to promote viral clearance. The H84T-BanLec CAR was stably expressed at high density on primary human NK cells during ex vivo expansion. H84T-BanLec CAR-NK cells inhibited viral entry of S-protein pseudotyped lentivirus into 293T cells expressing ACE2, the receptor for SARS-CoV-2. NK cells were activated to secrete inflammatory cytokines when in culture with virally infected cells. H84T-BanLec CAR-NK cells therefore hold promise as an off-the-shelf cell therapy for patients suffering from COVID-19.